Chronic digitalis therapy in patients before heart transplantation is an independent risk factor for increased posttransplant mortality - Rivinius, Rasmus; Helmschrott, Matthias; Ruhparwar, Arjang; Rahm, Ann-Kathrin; Darche, Fabrice Fernand; Thomas, Dierk; Bruckner, Thomas; Ehlermann, Philipp; Katus, Hugo; Dösch, Andreas (Therapeutics and clinical risk management, 2017)
Objectives: Digitalis therapy (digoxin or digitoxin) in patients with heart failure is subject to an ongoing debate. Recent data suggest an increased mortality in patients receiving digitalis. This study investigated the effects of chronic digitalis therapy prior to heart transplantation (HTX) on posttransplant outcomes.Patients and methods: This was a retrospective, observational, single-center study. It comprised 530 adult patients who were heart-transplanted at Heidelberg University Hospital between 1989 and 2012. Patients with digitalis prior to HTX (≥3 months) were compared to those without (no or <3 months of digitalis). Patients with digitalis were further subdivided into patients receiving digoxin or digitoxin. Primary outcomes were early posttransplant atrial fibrillation and mortality.Results: A total of 347 patients (65.5%) had digitalis before HTX. Of these, 180 received digoxin (51.9%) and 167 received digitoxin (48.1%). Patients with digitalis before HTX had a significantly lower 30-day (P=0.0148) and 2-year (P=0.0473) survival. There was no significant difference between digoxin and digitoxin in 30-day (P=0.9466) or 2-year (P=0.0723) survival. Multivariate analysis for posttransplant 30-day mortality showed pretransplant digitalis therapy as an independent risk factor (hazard ratio =2.097, CI: 1.036–4.248, P=0.0397). Regarding atrial fibrillation in the early posttransplant period, there was neither a statistically significant difference between patients with and without digitalis (P=0.1327) nor between patients with digoxin or digitoxin (P=0.5867).Conclusion: Digitalis in patients before HTX is an independent risk factor for increased posttransplant mortality. Keywords: atrial fibrillation, digitalis, heart transplantation, mortality